A Case of Isolated External Iliac Vein Compression Syndrome and the Role of Advanced Imaging. (August 2020) - Mukarram, Osama; Dahal, Khagendra; Azrin, Michael; Lee, Juyong
Isolated external iliac vein compression syndrome is an uncommon cause of nonthrombotic venous stenosis that causes chronic venous hypertension leading to painful swelling, skin discoloration, and ulcer formation. We present a case of an 86-year old man with refractory lower extremity edema for several years who had been treated with diuretics and antibiotics without relief of symptoms. With the help of invasive and noninvasive imaging modalities, we were able to diagnose and manage isolated nonthrombotic left external iliac vein stenosis as a result of ipsilateral external iliac artery compression.